W1/O/W2 emulsion stabilized by β-lactoglobulin/exopolysaccharides/epigallocatechin gallate complex: Protective effects on Lactobacillus plantarum A81 during storage, pasteurization and gastrointestinal digestion - Cuicui Duan; Yi Zhang; Hongru Wang; Siyang Sui; Hui Liu; Cheng Wu; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Chemistry, 2026)

Key aroma-active compounds and machine learning classification of chestnut baijiu revealed by molecular sensory, docking, and pathway analyses - Dan Li; Xinyue Zhang; Xiaohui Dou; Yujia Li; Yuchen Hou; Fumin Ma; Cuicui Duan; Xiaolei Li (Food Research International, 2026)

Exploration of the hypoglycemic effect and mechanism of Lactobacillus plantarum LH36 on type 2 diabetic mice through intestinal flora and non-targeted metabolomics - Cuicui Duan; Hui Liu; Siyang Sui; Hongru Wang; Yinfei Xing; Yixue Sun; Lifan Liu; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2026)

Structural identification and antioxidant activity of soybean protein isolate-exopolysaccharides-chlorogenic acid ternary complex - Cuicui Duan; Siyang Sui; Hongru Wang; Hui Liu; Yiming Yang; Yixue Sun; Lifan Liu; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2026)

Study on the characteristics of W1/O/W2 emulsion delivery system stabilized by soybean protein isolate/(−)-epigallocatechin gallate/exopolysaccharides complex - Cuicui Duan; Cheng Wu; Hui Liu; Siyang Sui; Hongru Wang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Research International, 2026)

Deciphering flavor profile and metabolic pathways in black chokeberry co-fermented by Lactiplantibacillus plantarum and Hansenula sp. via integrated volatilomics and metabolomics - Xiaolei Li; Wanxin Wang; Yujia Li; Fumin Ma; Cuicui Duan; Dan Li (Food Research International, 2026)

Enhanced suppression of retrogradation and digestibility in waxy rice starch by engineered mutants of GtfC type 4,6-α-glucanotransferase from Geobacillus sp. - Dan Li; Yuwei Liu; Cuicui Duan; Fumin Ma; Byung-Hoo Lee; Xiaolei Li (Food Bioscience, 2026)

Revealing the key aroma-active compounds and their potential metabolic pathways in Hongqu rice vinegar by integrating instrumental, sensory and statistical analysis - Xiaolei Li; Yujia Li; Fumin Ma; Cuicui Duan; Dan Li (International Journal of Gastronomy and Food Science, 2026)

Detection of soluble solids content in mold-infected Hami melons based on hyperspectral image fusion spectral-texture using 3DCNN-TexNet-Att - MingHui Zhang; Benxue Ma; Fumin Dang; Fujia Dong; Ying Xu; Fan Wu (Postharvest Biology and Technology, 2026)

Plasma surface modification for inhibiting biofilm formation and immunomodulatory treatment of implant-related infections - Nongyang Yan; Fumin Yuan; Shuang Tan; Tengfei Li; Bichong Dai; Xiaoxue Bai; Wenchong Ouyang; Zhixin Ma; Hua Qiu; Zhengwei Wu; Zhenkun Xia (Chemical Engineering Journal, 2025)

Low-cost detection method for early-stage mildew in Hami melons based on hyperspectral image reconstruction using Sim-MST++ - Fujia Dong; Ying Xu; Benxue Ma; Fumin Dang; Yujie Li; Minghui Zhang; Fan Wu; Guowei Yu (Food Control, 2025)

Global synthesis of nitrogen management in sugarcane systems: Decoding climate-soil-management drivers of Brazil-China contrasts - Xiaomai Yuan; Shengsen Zhou; Fumin Wei; Li Ma; Yongfeng Sun; Dingjiao Peng; Run Liang; Yibao Luo; Baoshan Chen; Wei Yao; Ziting Wang (Field Crops Research, 2025)

Functional properties and sensitization of β-lactoglobulin were improved by covalent binding with exopolysaccharides and (−)-epigallocatechin gallate - Cuicui Duan; Yi Zhang; Cheng Wu; Siyang Sui; Hui Liu; Hongru Wang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Evolution of Uniaxial Compressive Properties of Weathered Granite with Varying Weathering and Mineral Content - Peng Lin; Fumin Liu; Ruiyang Ma; Zhaoyang Wang; Huihui Xie; Jintao Kang (Geotechnical and Geological Engineering, 2025)

Exploration of the structural features and anti-oxidative activity of whey protein hydrolysates produced by Lactiplantibacillus plantarum - Cuicui Duan; Shunan Hu; Cheng Wu; Yi Zhang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Athyrium multidentatum (Doll.) Ching polysaccharide coated zein nanoparticles for oral delivery of resveratrol: Fabrication, characterization, stability and in vitro digestion - Fumin Ma; Wenxin Lv; Lei Wu; Cuicui Duan; Xiaolei Li; Dan Li (Food Bioscience, 2025)

An emulsion gel made by waxy maize starch hydrogel incorporated with tea polyphenols/exopolysaccharides: Structure and stability properties, antioxidant and delivery function - Cuicui Duan; Shunan Hu; Ran Wang; Cheng Wu; Yi Zhang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

High-performance flexible wearable electronics for sheep physiological information wireless sensing and health assessment - Maosong Yin; Ruiqin Ma; Wentao Huang; Fumin Chi; Qinan Zhao; Mengjie Zhang (Computers and Electronics in Agriculture, 2025)

Ce-doped TiO2 supported RuO2 as efficient catalysts for the oxidation of HCl to Cl2 - Jiahui Liu; Fangyuan Dong; Yaqi Huang; Yanghe Fu; Xinqing Lu; Rui Ma; Fumin Zhang; Shuhua Wang; Weidong Zhu (Journal of Environmental Sciences, 2025)

An exploration on the structural characteristics and antioxidant activities of casein hydrolysates fermented by Lactiplantibacillus plantarum A56 and A157 - Cuicui Duan; Lingfang Zhang; Cheng Wu; Yi Zhang; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

An exploration of the interaction, structural characterization and anti-oxidative properties of proanthocyanidin and beta-lactoglobulin complex - Cuicui Duan; Mengchun Qin; Lifan Liu; Yixue Sun; Lin Cai; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Multispectral analysis and molecular docking to predict the mechanism of molecular interactions of curcumin, zein and fucoidan complexes - Yaqi Lu; Xiang Cai; Wenxin Lv; Cuicui Duan; Xiaolei Li; Fumin Ma; Dan Li (Journal of Food Engineering, 2024)

A fast and efficient phenotyping method to estimate sugarcane stalk bending properties using near-infrared spectroscopy - Fumin Ma; Maoyao Wang; Ning Yan; Muhammad Adnan; Fuhong Jiang; Qian Hu; Guanyong He; Yinjuan Shen; Yan Wan; Yixian Yang; Shaojing Liang; Xiaoru Chen; et al. (European Journal of Agronomy, 2024)

Thiolation modification of pectin effectively alleviates the weakening of wheat gluten network caused by natural pectin - Jinfeng Chen; Yanli Cui; Wanlu Shi; Fumin Yang; Yunxiang Ma; Shenggui Zhang; Yue Wang (Food Hydrocolloids, 2023)

Fucoidan extracted by different methods and bound to zein loaded curcumin nanoparticles: Preparation, physicochemical stability, and in vitro functions - Yaqi Lu; Di An; Wenxin Lv; Xiang Cai; Fumin Ma; Dan Li (Food Bioscience, 2023)

Compound treatment of thiolated citrus high-methoxyl pectin and sodium phosphate dibasic anhydrous improved gluten network structure - Jinfeng Chen; Yanli Cui; Shenggui Zhang; Yunxiang Ma; Fumin Yang (Food Chemistry, 2023)

pH-responsive in situ gelling properties of thiolated citrus high-methoxyl pectin and its potential gel mechanism - Jinfeng Chen; Yanli Cui; Fumin Yang; Shenggui Zhang; Yunxiang Ma; Jia Liu (Food Research International, 2023)

High-resolution numerical simulation of topographic influence on the heavy rainfall of Typhoon Rammasun - Xianling Jiang; Fumin Ren; Wenyu Qiu; Liguang Wu; Zhuguo Ma; Xun Li (Theoretical and Applied Climatology, 2022)

Exploring the environmental properties and resource utilization of construction waste in Beijing-Tianjin-Hebei region - Shuxin Hu; Fumin Ren; Jinming Jia; Can Cui; Changhong Guo; Nana Cui; Li Ma; Han Si; Tong Lu; Guotao Liu; Boyu Zhang; Junshi Liu (Environmental Science and Pollution Research, 2022)

Applying rail transit construction waste to make building materials: using the theory of sustainable development - Jinming Jia; Fumin Ren; Xiao Wei; Yinghao Gao; Gao Qi; Fuan Li; Ma Li; Changan Guo (Environmental Science and Pollution Research, 2022)

Densely sampled phylogenetic analyses of the Lesser Short‐toed Lark ( Alaudala rufescens ) — Sand Lark ( A. raytal ) species complex (Aves, Passeriformes) reveal cryptic diversity - Fatemeh Ghorbani; Mansour Aliabadian; Ruiying Zhang; Martin Irestedt; Yan Hao; Gombobaatar Sundev; Fumin Lei; Ming Ma; Urban Olsson; Per Alström (Zoologica Scripta, 2020)
The taxonomy of the Lesser/Asian Short‐toed Lark Alaudala rufescens – cheleensis complex has been debated for decades, mainly because of minor morphological differentiation among the taxa within the complex, and different interpretations of the geographical pattern of morphological characters among different authors. In addition, there have been few studies based on non‐morphological traits. It has recently been suggested based on a molecular study of the lark family Alaudidae that the Sand Lark A. raytal is nested within this complex. We here analysed mitochondrial cytochrome b (cyt b ) from 130 individuals across the range of this complex (hereafter called Alaudala rufescens–raytal complex), representing all except two of the 18 currently recognized subspecies. We also analysed 11 nuclear markers from a subsample of these individuals, representing all of the clades found in the cyt b tree. Five primary clades were recovered, which confirmed that A. raytal is nested within this complex. Divergence time estimates among these five clades ranged from 1.76 to 3.16 million years (my; 95% highest posterior density [HPD] 1.0–4.51 my) or 1.99–2.53 my (95% HPD 0.96–4.3 my) in different analyses. Only four of the currently recognized subspecies were recovered as monophyletic in the cyt b tree. Our results call for a taxonomic revision, and we tentatively suggest that at least four species should be recognized, although we stress the need for an approach integrating molecular, morphological and other data that are not yet available.

Characteristics and Preliminary Causes of Tropical Cyclone Extreme Rainfall Events over Hainan Island - Xianling Jiang; Fumin Ren; Yunjie Li; Wenyu Qiu; Zhuguo Ma; Qinbo Cai (Advances in Atmospheric Sciences, 2018)

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Interaction Between Umami Peptide and Taste Receptor T1R1/T1R3 - Yali Dang; Xinchang Gao; Aiying Xie; Xueqian Wu; Fumin Ma (Cell Biochemistry and Biophysics, 2014)